Câhiliye Döneminde fütüvvet - Özkardaş, Kazım Berkay (My University, 2024)
Câhiliye Döneminde Fütüvvet isimli bu çalışma, fütüvvet kavramının tarih sahnesine çıktığı Câhiliye döneminde hangi anlamlara geldiğini açıklamayı hedeflemektedir. Yüzyıllar boyunca İslâm düşüncesinin merkezî kavramlarından biri olan fütüvvetin anlam küresi, fetâ ve çekimleri üzerinden Câhiliye döneminde oluşmaya başlamıştır. Bu dönemde herhangi bir değer yükü taşımaksızın, yalnızca genç anlamında kullanıldığı gibi cömert, iyi savaşan ve kabilesinin ihtiyaçları için her türlü fedâkârlığı yapmaktan çekinmeyen gençler için de fetâ lafzı kullanılmaktadır. Bu kişiler reislik ve danışma meclisi üyeliği gibi üst düzey görevler icrâ edebilirken yaraları tedavi eden sıhhiye sınıfı mensubu yahut piyade de olabilmekteydi. Bütün bunların yanında fetâlar kaynaklarda insanî meziyetleriyle de anılmıştır. Cömertlik, yardımseverlik, ölçülü konuşma, sözünde durma ve ölümü kabullenme onların başta gelen hasletlerindendir. Fetâlar Câhiliye anlatılarında aşk hayatları ve içki meclislerindeki hikâyeleriyle de gündeme gelmiştir.

This work, named “Futuwwa in the Jahiliyyah Period”, aims to explain the meanings of the concept of futuwwa during the Jahiliyyah period when it first appeared on the historical stage. The semantic sphere of futuwwa, which has been one of the central concepts of Islamic thought for centuries, began to form during the Jahiliyyah period through the terms “fata” and its plural and feminine forms. In this period, the word was used not only in the sense of “young” without carrying any connotation but also referred to young men who were generous, good fighters, and did not hesitate to make any sacrifice for the needs of their tribe. These individuals could hold high-level positions in the tribal hierarchy such as leadership and membership in the advisory council, while they could also be members of the medical class treating wounds or infantrymen. Besides all these, the fatas are also mentioned in the sources with their human virtues. Generosity, helpfulness, speaking after careful thought, keeping one’s word, and easily accepting death are among their foremost qualities. In the narratives of the Jahiliyyah, fatas also came up with stories about their love lives and the tales in the drinking sessions. In addition, the terms fata and its plural and feminine forms were also used for slaves/ concubines and young animals. The dual form of the word “fatayân” was used to denote night and day.
Futuwwa in the Jahiliyyah Period
Keywords: Cahiliye; Futuwwa; Futuwwa (Islamic social groups); Fütüvvet; Fütüvvet (İslam sosyal grupları); History; History of Concepts; Islam; İslam Tarihi; İslamiyet; Jahiliyyah; Kavram Tarihi History of Islam; Savaş; Tarih; War